Universalitas Bahasa dalam Konteks PBA li al-Marhalah al-Ibtidā'iyyah - Nanik Setyowati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2019)
This study aims to generalize the concept of the universality of language in the context of learning Arabic in Indonesia. The method used this research is descriptive qualitative. Already Arabic learning at the basic level does not use conventional approaches and methods in this era, but a teacher must be more constructive in managing learning, one of them is the approach of universality of language. A good Arabic learning must have an universality of language value. The universality language is a system of sound symbols that must be complemented by the full and systematic dimensions of language. The principles which are have to be folowwed in the universality of language such as syntac, phonology, morphology and semantic principles. Thus, PBA contestation in basic lavel using the system of language universality will be better to improve students Arabic language skills.